Mediating towards digital inclusion: the monitors of internet access places - Aires,Luísa (2018)
Local dynamics play a key role in individual and collective empowerment for digital literacy and citizenship. This paper presents the results and reflections from a broader investigation into the public Internet access places in Portugal in the inland municipalities of the country's coast, undertaken by ObLID Network. Specifically, we intend to reflect on the actual mission of these places and reveal the actual profile, activities and training needs of their monitors and coordinators. In the first stage of the empirical study, several documents available on the Internet Spaces Network are analyzed. In the second stage, a questionnaire was applied to monitors and coordinators of the Internet access places, in seventeen Portuguese municipalities. The research results warn of the need to redefine and clarify the social and educational value of Internet spaces, indicating that the dominant activities of monitors in the Internet access places do not induce the foster of literacy and digital inclusion of the most vulnerable groups. In this context, actions are proposed that can contribute to improving the mission of Internet places, as well as the training quality of their monitors and coordinators. Internet Access Spaces, made available by municipalities, should be used to promote digital literacy programs, for individuals and groups.